2015
DOI: 10.1371/journal.pone.0124007
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Inhibits Tumor Promoter-Induced MMP-9 Expression by Blocking AP-1 via Suppression of ERK and JNK Pathways in Gastric Cancer Cells

Abstract: Cell invasion is a crucial mechanism of cancer metastasis and malignancy. Matrix metalloproteinase-9 (MMP-9) is an important proteolytic enzyme involved in the cancer cell invasion process. High expression levels of MMP-9 in gastric cancer positively correlate with tumor aggressiveness and have a significant negative correlation with patients’ survival times. Recently, mechanisms suppressing MMP-9 by phytochemicals have become increasingly investigated. Chrysin, a naturally occurring chemical in plants, has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 37 publications
2
51
0
Order By: Relevance
“…14,16,32 In the present study, chrysinNPs were observed to have anticancer effects in A549-derived tumor tissues. In fact, chrysin-NPs inhibited cell proliferation and induced apoptosis in tumor tissues ( Figure 6).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…14,16,32 In the present study, chrysinNPs were observed to have anticancer effects in A549-derived tumor tissues. In fact, chrysin-NPs inhibited cell proliferation and induced apoptosis in tumor tissues ( Figure 6).…”
Section: Discussionmentioning
confidence: 49%
“…Chrysin is a natural active component found in various herbs, mushroom, and propolis 2 and has anti-inflammatory, 3,4 antiaging, 5 antiviral, 6 antioxidant, [7][8][9] antidiabetes, 10 antiaromatase, 11,12 and anticancer [13][14][15][16] activities. Accordingly, it is widely held that chrysin has potential pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a crucial c-Jun and c-Fos binding site, AP-1 is located in the promoter region of inducible type of MMP genes. Blocking in the AP-1 binding activity prevents tumor promoter-induced MMP-9 transcription [45]. Besides, NF-κB and SP-1 transcription factors also play a co-activators role in the regulation of MMP-2 and MMP-9 [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…The MMP family comprises 24 zincdependent endopeptidases, and serves important roles in tumor metastasis and MMP26 is associated with the invasion and metastasis of non-small cell lung cancer (34)(35)(36). It has been reported that the expression of MMPs is regulated by MAPK pathways (37,38). To confirm whether ERK and p38 signaling pathway is involved in this situation, we applied specific inhibitors for ERK and p38, respectively, to the FGF18-stimulated H460 cells.…”
Section: Discussionmentioning
confidence: 99%